Development of the Interdisciplinary and Interprofessional Course Concept “Advanced Critical Illness Life Support” - Michael, Mark; Biermann, Henning; Gröning, Ingmar; Pin, Martin; Kümpers, Philipp; Kumle, Bernhard; Bernhard, Michael (Frontiers in Medicine, 2022)
The Advanced Critical Illness Life Support (ACiLS) course was developed on behalf of the German Society for Interdisciplinary Emergency and Acute Medicine (DGINA). The goal of the ACiLS course is to provide a nationally recognized and certified life support course that teaches medical professionals the key principles of initial care of critically ill patients in the emergency department, including the (PR_E )AUD2IT-algorithm. It is designed for interdisciplinary and multi-professional staff in the resuscitation room to optimize patient safety and outcome. ACiLS includes a new blended learning concept with a theoretical part as comprehensive e-learning and a two-day practical part with strong focus on team training in scenarios and workshops. The course format was conceived to balance best teaching practices within the limited instructional time and resources available. This article describes the development of the ACiLS course and provides an overview of its future implementation.